2012
DOI: 10.1055/s-0031-1295836
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin upregulates hepatocyte CMKLR1 which is reduced in human fatty liver

Abstract: Chemokine-like receptor 1 (CMKLR1) ligands chemerin and resolvin E1 are suggested to have a role in non-alcoholic fatty liver disease (NAFLD). Here, expression of CMKLR1 in liver cells and NAFLD was studied. CMKLR1 was detected in primary human hepatocytes (PHH), Kupffer cells, bile-duct cells and hepatic stellate cells. In human and rodent fatty liver and in fibrotic liver of mice fed a methionine-choline deficient diet CMKLR1 was reduced. Hepatocytes are the major cells in the liver and effects of adipokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Chemerin acts by binding the G protein-coupled receptor, chemokine receptor-like 1 (CMKLR1) (also known as chemerin receptor 23 (ChemR23)) [7,26], expressed by a variety of cells [26,27,28,29]. CMKLR1 was highly abundant in the liver and is expressed by primary human hepatocytes, hepatic stellate cells, Kupffer cells, and bile duct cells [30]. The data with respect to chemerin and CMKLR1 mRNA is very limited and equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Chemerin acts by binding the G protein-coupled receptor, chemokine receptor-like 1 (CMKLR1) (also known as chemerin receptor 23 (ChemR23)) [7,26], expressed by a variety of cells [26,27,28,29]. CMKLR1 was highly abundant in the liver and is expressed by primary human hepatocytes, hepatic stellate cells, Kupffer cells, and bile duct cells [30]. The data with respect to chemerin and CMKLR1 mRNA is very limited and equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…CMKLR1 was detected in primary human hepatocytes, Kupffer cells, bile-duct cells and hepatic stellate cells, but was decreased in human and rodent fatty liver and in fibrotic liver of mice. Adiponectin strongly upregulated CMKLR1 in primary human hepatocytes and in liver tissue while hepatic CMKLR1 was suppressed in the liver of adiponectin deficient mice (86). A recent study showed that pretreatment with resolvin D1 attenuated endoplasmic reticulum stress-induced apoptosis and decreased caspase 3 activity in HepG2 cells (87).…”
Section: Omega-3 Fatty Acids and Resolution Of Inflammation In Nafld:mentioning
confidence: 98%
“…Mechanistically, autophagy activation by adiponectin causes digestion of Bax, thereby preventing caspase activation. 6) In addition, adiponectin enhances the expression of chemokine-like receptor 1 and CXCL8 by adipoR1 signaling in human hepatocytes, 17,18) which behave as survival factors in the liver. Adiponectin also attenuates ceramide accumulation in liver.…”
Section: Anti-apoptotic and Pro-survival Effects Of Adiponectin In LImentioning
confidence: 99%